Изучение практики обучения арифметическим действиям в специальных (вспомогательных) школах республики - Искандарян, С. С.
The article presents the results of arithmetic operations’ practice st udy at the © ecial (auxiliary) schools of the Republic, the problem of insuffi cient st udying of the issue related to the learning methods, the means and the optimization of conditions. The research reveals all the problem areas.
Keywords: Специальное (дефектологическое) образование